PEMBENTUKAN CITRA POSITIF PERUSAHAAN MELALUI CYBER PUBLIC RELATIONS - MS, Darwadi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.08.TAHUN 2019, 2019)
In this research, it was carried out to fulfill the objectives, namely to explain, explain, and discuss the new variants of public relations, namely cyberspace public relations or e-PR, as well as the sustainability of functions and performance assistance related to the development of positive images as opportunities to be discussed. Relationship between cyberspace is success. Things that cannot be solved physically by conventional public relations can be done by applying cyber community relations, and vice versa. In other words public relations and cyber public relations are interrelated and complementary in order to achieve public relations goals to advance the company or its shade organization.